Pengaruh Proses Rekrutmen Terhadap Kinerja Karyawan Pada PT. Bank Cimb Niaga Auto Finance Cabang Makassar - Tri Fira Yuniza; Anna Ashrawi Suhartini (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze employee performance at PT. CIMB Niaga Auto Finance Makassar Branch in realizing dominance in competition with other companies where these efforts are closely related to human resources which influence employee performance in the company and are capital assets in the company. The population targeted for this research are parties related to the performance of PT employees. CIMB Niaga Auto Finance Makassar Branch, a total of 39 people, and all of them became respondents using questionnaires and data analysis tools. The results of this research show that from the results of the analysis of employee performance at PT. CIMB Niaga Auto Finance Makassar branch, by looking at several aspects such as education, references, experience, health, work behavior, work characteristics and personal characteristics, found that all aspects of the assessment during the recruitment process had a very positive and significant influence on employee performance.